New soluble methylendioxy-phenoxy-substituted zinc phthalocyanine derivatives: Synthesis, photophysical and photochemical studies - Erdogmus, Ali; Nyokong, Tebello (PERGAMON-ELSEVIER SCIENCE LTD, 2009)
The syntheses of new three phthalonitriles (1, 2 and 3), together with photophysical and photochemical properties of the resulting peripherally and non-peripherally tetrakis- and octakis 3,4-(methylendioxy)-phenoxy-substituted zinc phthalocyanines (4, 5 and 6) are described for the first time. Complexes 4, 5 and 6 have been synthesized and characterized by elemental analysis, IR, H-1 NMR spectroscopy, electronic spectroscopy and mass spectra. Complexes 4, 5 and 6 have good solubility in organic solvents such as CHCl3, DCM, DMSO, DMF, THF and toluene and are mainly not aggregated (except for complex 6 in DMSO) within a wide concentration range. General trends are described for singlet oxygen, photodegradation, fluorescence quantum yields, triplet quantum yields and triplet life times of these complexes in DMSO and toluene. Complex 4 has higher singlet oxygen quantum yields, fluorescence quantum yields, triplet quantum yields and triplet life times than complexes 5 and 6. The effect of the solvents on the photophysical and photochemical parameters of the zinc(II) phthalocyanines (4, 5 and 6) are also reported. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Zinc phthalocyanines; Triplet quantum yield; Fluorescence quantum yield; Singlet oxygen; Photodynamic therapy; OXYGEN QUANTUM YIELDS; METAL-ION BINDING; FLUORESCENCE; METALLOPHTHALOCYANINES; ELECTROCHEMISTRY; COMPLEXES; PHOTOSENSITIZERS; CANCER; Chemistry; Crystallography